Changes in science attitudes, beliefs, knowledge and physiological arousal after implementation of a multimodal, cooperative intervention in primary school science classes. Issue 7 (13th August 2019) - Carroll, Annemaree; Gillies, Robyn M.; Cunnington, Ross; McCarthy, Molly; Sherwell, Chase; Palghat, Kelsey; Goh, Felicia; Baffour, Bernard; Bourgeois, Amanda; Rafter, Mary; Seary, Tennille
Abstract : Purpose: Student competency in science learning relies on students being able to interpret and use multimodal representations to communicate understandings. Moreover, collaborative learning, in which students may share physiological arousal, can positively affect group performance. This paper aims to observe changes in student attitudes and beliefs, physiology (electrodermal activity; EDA) and content knowledge before and after a multimodal, cooperative inquiry, science teaching intervention to determine associations with productive science learning and increased science knowledge. Design/methodology/approach: A total of 214 students with a mean age of 11 years 6 months from seven primary schools participated in a multimodal, cooperative inquiry, science teaching intervention for eight weeks during a science curriculum unit. Students completed a series of questionnaires pertaining to attitudes and beliefs about science learning and science knowledge before (Time 1) and after (Time 2) the teaching intervention. Empatica E3 wristbands were worn by students during 1 to 3 of their regularly scheduled class sessions both before and after the intervention. Findings: Increases in EDA, science knowledge, self-efficacy and a growth mindset, and decreases in self-esteem, confidence, motivation and use of cognitive strategies, were recorded post-intervention for the cohort. EDA was positively correlated with science knowledge, but negatively correlated with self-efficacy, motivation and use of cognitive strategies. Cluster analysis suggested three main clusters of students with differing physiological and psychological profiles. Practical implications: First, teachers need to be aware of the importance of helping students to consolidate their current learning strategies as they transition to new learning approaches to counter decreased confidence. Second, teachers need to know that an effective teaching multimodal science intervention can not only be associated with increases in science knowledge but also increases in self-efficacy and movement towards a growth mindset. Finally, while there is evidence that there are positive associations between physiological arousal and science knowledge, physiological arousal was also associated with reductions in self-efficacy, intrinsic motivation and the use of cognitive strategies. This mixed result warrants further investigation. Originality/value: Overall, this study proposes a need for teachers to counter decreased confidence in students who are learning new strategies, with further research required on the utility of monitoring physiological markers.